2017
DOI: 10.31018/jans.v9i1.1233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different orchard management practices on the growth and production of rejuvenated of pomegranates (Punica granatum L.) cv. Kandhari Kabuli

Abstract: Orchard management practices are the most important cultural tools for successful and sustainable cultivation of any fruit crop including pomegranate. Orchard management systems have an effect on growth, yield and fruit quality through their smoothening effects on the availability of nutrients, conservation of moisture and reduction of weed competition. Orchard management practices treatments viz., five orchard floor management treatments viz., T1: Grass mulch (10 cm thick), T2: Black polythene mulch, T3: Clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…The maximum TSS: Acid ratio (42.10%) was observed in T 1 , whereas minimum TSS: Acid ratio (21.86%) was observed in T 5 (Table 3). The results are in accordance with the earlier findings that percent TSS and other physicochemical characters increased significantly with severe pruning treatments (Hassani andRezaee, 2007 andSharma et al, 2017). Disease incidence on fruit and leaf surface: The present investigation revealed that the disease incidence in the fruit and leaf surface were affected significantly by all the pruning treatments over control.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The maximum TSS: Acid ratio (42.10%) was observed in T 1 , whereas minimum TSS: Acid ratio (21.86%) was observed in T 5 (Table 3). The results are in accordance with the earlier findings that percent TSS and other physicochemical characters increased significantly with severe pruning treatments (Hassani andRezaee, 2007 andSharma et al, 2017). Disease incidence on fruit and leaf surface: The present investigation revealed that the disease incidence in the fruit and leaf surface were affected significantly by all the pruning treatments over control.…”
Section: Methodssupporting
confidence: 82%
“…However, the effect of pruning treatments on the durations were non-significant and maximum disease incidence was recorded in T 5 (control). The results relating to the decrease in disease severity by different pruning treatments over control are in agreement with the findings of (Riedle, 2010) in grapes, (Lemus, 2010), in walnut (Yang, 2009) in persimmon and apricot Sharma et al (2017).…”
Section: Methodssupporting
confidence: 80%